Optical glass, preparation method thereof and optical element

By adjusting the molar percentage of specific cationic components, optical glass with a refractive index of 1.73 to 1.83, a small coefficient of thermal expansion, excellent devitrification resistance and chemical stability were prepared, which solved the problems of existing optical glasses being prone to cracking and insufficient chemical stability during processing, and met the performance needs of modern optoelectronic products.

CN119612959APending Publication Date: 2025-03-14HUBEI NEW HUAGUANG NEW INFORMATION MATERIALS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411748620.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Existing optical glasses are prone to cracking during processing, have a large thermal expansion coefficient, poor thermal shock resistance, and are also poor invasive to liquids in the environment and lack chemical stability, making it difficult to meet the needs of modern optoelectronic products.

Method used

An optical glass of a specific composition is used, which contains cationic components such as Si4+, Ti4+, Nb5+, Na+, K+, Zr4+, Ba2+, Sr2+, Al3+, Y3+ and Sb3+. By adjusting the molar percentage of these components, an optical glass with a refractive index of 1.73 to 1.83, a small coefficient of thermal expansion, a high resistance to devitrification and chemical stability are prepared.

Benefits of technology

It realizes efficient processing of optical glass, improves the yield rate and thermal shock resistance of glass, enhances its resistance to environmental erosion, and meets the high requirements of modern optoelectronic products for optical glass performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005165133520000111
    Figure BDA0005165133520000111
  • Figure BDA0005165133520000121
    Figure BDA0005165133520000121
  • Figure BDA0005165133520000131
    Figure BDA0005165133520000131
Patent Text Reader

Abstract

The invention provides optical glass, a preparation method thereof and an optical element. The optical glass comprises the following components in percentage by cation mole: 36-47% of Si < 4 + >; 26 to 31.5 percent of Ti < 4 + >; 3-9% of Nb < 5 + >; 4.5%-10% of Na < + >; 4-7% of K < + >; zr < 4 + >: 3-4.2%; 5 to 8.7 percent of Ba < 2 + >; 2.3 to 4% of Sr < 2 + >; 0-3% of Al < 3 + >; 0-3% of Y < 3 + >; 0 to 0.03 percent of Sb < 3 + >; the refractive index of the optical glass ranges from 1.73 to 1.83, and the abbe number of the optical glass ranges from 20 to 30. The optical glass provided by the invention has a refractive index of 1.73-1.83, a small thermal expansion coefficient, and excellent devitrification resistance, chemical stability and weather resistance. Therefore, the optical glass provided by the invention is convenient to process and excellent in chemical stability, and can meet the requirements of modern novel photoelectric products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to optical glass and a preparation method thereof and an optical element, belonging to the field of optical glass. Background Art

[0002] With the development of the optoelectronic industry, the requirements for miniaturization, lightness and high performance of optical components have been put forward, which has led to an increasing demand for optical glass with a refractive index of 1.73 to 1.83 and an Abbe number of 20 to 30. In recent years, optical components and optical instruments have developed rapidly in terms of digitization, integration and high precision, which has put forward higher requirements on the performance of optical glass used in optical components of optical instruments and equipment.

[0003] Optical glass is prone to cracking during processing due to its large thermal expansion coefficient, which reduces the yield of the glass. It also leads to poor thermal shock resistance. Therefore, optimizing the thermal expansion coefficient of glass is crucial to improving the yield of glass.

[0004] Optical glass will be corroded by various liquids in the environment (such as acid, alkali, water, etc.) during processing or use. Therefore, the resistance of optical glass to these corrosions, that is, the chemical stability of optical glass, is crucial to the accuracy and life of the instrument.

[0005] In addition, as the opportunities for continuous outdoor use of photographic equipment such as digital cameras and digital video cameras, surveillance cameras, and vehicle-mounted cameras using optical systems are increasing, lenses and the like used in optical systems for these applications are required to be durable enough to withstand wind, rain, chemicals, and the like.

[0006] The optical glasses disclosed in patent applications CN104981439A, CN108178509A, CN101636359A, etc. all have P 5+ Ingredients, P 5+ It is easy to corrode precious metal containers such as platinum, especially phosphate glass containing alkali metals. 5 + It is easy to volatilize under low temperature, affecting the optical stability of glass.

[0007] The optical glass disclosed in patent applications CN109790060A, CN107963808A, etc. contains a high content of La. 3+ , La 3+ The relative molecular mass is very large, and the content of La is high 3+ This will cause the specific gravity of the glass to be too high.

[0008] The optical glass disclosed in patent application CN102471130A etc. contains Li + , Li +It is detrimental to the acid resistance and thermal expansion coefficient of the glass, and causes corrosion to melting containers (such as platinum crucibles). Summary of the invention

[0009] Problem that the invention aims to solve

[0010] In view of the technical problems disclosed in the prior art, the present invention first provides an optical glass having a refractive index of 1.73 to 1.83, a small thermal expansion coefficient, and excellent devitrification resistance and chemical stability.

[0011] The present invention also provides a method for preparing optical glass. The preparation method is simple and easy to implement, the raw materials are easy to obtain, and the method is suitable for mass production.

[0012] Solutions for solving problems

[0013] The present invention provides an optical glass comprising the following components in terms of cation molar percentage:

[0014] Si 4+ : 36~47%;

[0015] Ti 4+ : 26~31.5%;

[0016] Nb 5+ : 3~9%;

[0017] Na + : 4.5~10%;

[0018] K + : 4~7%;

[0019] Zr 4+ : 3~4.2%;

[0020] Ba 2+ : 5~8.7%;

[0021] Sr 2+ : 2.3~4%;

[0022] Al 3+ : 0~3%;

[0023] Y 3+ : 0~3%;

[0024] Sb 3+ :0~0.03%;

[0025] The refractive index of the optical glass is 1.73-1.83, and the Abbe number is 20-30.

[0026] According to the optical glass of the present invention, the optical glass comprises the following components in terms of cation molar percentage:

[0027] Si 4+ : 38~46.5%;

[0028] Ti 4+ : 26~31%;

[0029] Nb 5+ : 4~8%;

[0030] Na + : 5~9%;

[0031] K + : 4.5~6.5%;

[0032] Zr 4+ : 3-4%;

[0033] Ba 2+ : 5.3~8.2%;

[0034] Sr 2+ : 2.5~4%;

[0035] Al 3+ : 0~1%;

[0036] Y 3+ : 0~1%;

[0037] Sb 3+ :0.01~0.02%.

[0038] According to the optical glass of the present invention, the optical glass comprises the following components in terms of cation molar percentage:

[0039] Si 4+ : 39~46%;

[0040] Ti 4+ : 26.5~30.5%;

[0041] Nb 5+ : 4.5~7.5%;

[0042] Na + : 5.5~8.5%;

[0043] K + : 5~6%;

[0044] Zr 4+ : 3-4%;

[0045] Ba 2+ : 5.5~8%;

[0046] Sr 2+ : 2.5~3.5%;

[0047] Al 3+ : 0~0.5%;

[0048] Y 3+ : 0~0.5%;

[0049] Sb 3+ :0.01~0.02%.

[0050] According to the optical glass of the present invention, the optical glass does not contain F - , P 5+ 、 5+ , Gd 3+ , Li + ,La 3 + ,Ge 4+ 、Te 4+ One or a combination of two or more.

[0051] According to the optical glass of the present invention, wherein Ti 4+ With Si 4 The molar percentage ratio of Ti 4+ / Si 4 0.55~0.85;

[0052] Nb 5+ With Ti 4+ The molar percentage ratio of Nb 5+ / Ti 4+ It is 0.1~0.32.

[0053] According to the optical glass of the present invention,

[0054] The density of the optical glass is 3.40 g / cm 3 the following;

[0055] The coloration degree λ of the optical glass 80 / λ5,λ 80 is below 440nm, and λ5 is below 365nm;

[0056] The hardness HK of the optical glass is 500×10 7 Pa or above.

[0057] According to the optical glass of the present invention,

[0058] The water resistance stability of the optical glass is level 1;

[0059] The acid resistance stability of the optical glass is level 1;

[0060] The anti-crystallization performance of the optical glass is A-B grade;

[0061] The bubble degree of the optical glass is 0-1 level.

[0062] The present invention also provides a method for preparing the optical glass according to the present invention, which comprises weighing the components of the optical glass according to a proportion, mixing them evenly, melting them, and then pouring or leaking them into a molding mold, or directly pressing them into shape.

[0063] The present invention also provides an optical preform, comprising the optical glass according to the present invention.

[0064] The present invention also provides an optical element, comprising the optical glass according to the present invention.

[0065] Effects of the Invention

[0066] The optical glass of the present invention has a refractive index of 1.73 to 1.83, a small thermal expansion coefficient, and excellent devitrification resistance, chemical stability and weather resistance. Therefore, the optical glass of the present invention is an optical glass that is easy to process and has excellent chemical stability, and can meet the needs of modern new optoelectronic products.

[0067] The preparation method of the optical glass of the present invention is simple and easy to implement, the raw materials are easy to obtain, and it is suitable for mass production. DETAILED DESCRIPTION

[0068] Various exemplary embodiments, features and aspects of the present invention will be described in detail below. The word "exemplary" used here means "used as an example, embodiment or illustrative". Any embodiment described here as "exemplary" is not necessarily interpreted as being superior or better than other embodiments.

[0069] In addition, in order to better illustrate the present invention, numerous specific details are provided in the following specific embodiments. It should be understood by those skilled in the art that the present invention can be implemented without certain specific details. In other examples, methods, means, equipment and steps well known to those skilled in the art are not described in detail in order to highlight the subject matter of the present invention.

[0070] Unless otherwise stated, the units used in this specification are all international standard units, and the numerical values ​​and numerical ranges appearing in the present invention should be understood to include the inevitable systematic errors in industrial production.

[0071] In this specification, the word "may" means both performing a certain process and not performing a certain process.

[0072] In this specification, the references to "some specific / preferred embodiments", "other specific / preferred embodiments", "embodiments", etc., mean that the specific elements (e.g., features, structures, properties and / or characteristics) described in connection with the embodiments are included in at least one embodiment described herein, and may or may not exist in other embodiments. In addition, it should be understood that the elements may be combined in various embodiments in any suitable manner.

[0073] In this specification, the numerical range expressed using "a numerical value A to a numerical value B" means a range including the endpoints numerical values ​​A and B.

[0074] The present invention provides an optical glass comprising the following components in terms of cation molar percentage:

[0075] Si 4+ : 36~47%;

[0076] Ti 4+ : 26~31.5%;

[0077] Nb 5+ : 3~9%;

[0078] Na + : 4.5~10%;

[0079] K + : 4~7%;

[0080] Zr 4+ : 3~4.2%;

[0081] Ba 2+ : 5~8.7%;

[0082] Sr 2+ : 2.3~4%;

[0083] Al 3+ : 0~3%;

[0084] Y 3+ : 0~3%;

[0085] Sb 3+ :0~0.03%;

[0086] The refractive index of the optical glass is 1.73-1.83, and the Abbe number is 20-30.

[0087] The composition of the optical glass of the present invention is described in detail below. The content of each glass component and the total content are expressed in terms of cationic molar percentage unless otherwise specified. In addition, in the following description, when a value below or above a specified value is mentioned, the specified value is also included.

[0088] Si 4+ It is the skeleton of optical glass. As a glass network generator, it has the function of maintaining the chemical stability of glass and improving the resistance of glass to devitrification. 4+ When the content is less than 36%, it is difficult to achieve the above effect. 4+ The lower limit of the content of Si is 36%, preferably 38%, and more preferably 39%; in terms of cation molar percentage, when Si 4+ When the content of Si is higher than 47%, the glass melting property decreases and the transition temperature increases. 4+ The upper limit of the content is 47%, preferably 46.5%, and more preferably 46%.

[0089] Ti 4+ It has the function of increasing the refractive index and dispersion of glass, and can participate in the formation of glass network. The appropriate amount of introduction can make the glass more stable and reduce the viscosity of the glass. In terms of cation molar percentage, the present invention introduces more than 26% Ti 4+ To obtain the above effects, Ti is preferably 4+ The lower limit of the content is 26.5%; but a large amount of Ti is introduced 4+ After that, the transmittance of the short-wave portion of the visible light region of the glass will be reduced, and the crystallization tendency of the glass will increase. Therefore, in the present invention, Ti is calculated by cation molar percentage. 4+ The upper limit of the content is 31.5%, preferably 31%, and more preferably 30.5%.

[0090] In some embodiments of the present invention, when Ti 4+ With Si 4 The molar percentage ratio of Ti 4+ / Si 4+ Too low, the glass's melting point will decrease, and the stripe degree will deteriorate. 4+ With Si 4 The molar percentage ratio of Ti 4+ / Si 4+ Too high, the chemical stability and optical transmittance of the glass decrease, and the density increases. 4+ / Si 4+ 0.55~0.85, preferably Ti 4+ / Si 4+ 0.6 to 0.8, more preferably Ti 4+ / Si 4+ It is 0.65~0.75.

[0091] Nb 5+It is a high refractive and high dispersion component, which can improve the resistance of glass to devitrification. In terms of cation molar percentage, the present invention introduces more than 3% Nb 5+ To obtain the above effect, if Nb 5+ If the content of Nb exceeds 9%, the thermal stability and chemical stability of the glass will decrease, and the optical transmittance will decrease. 5+ The content is 3 to 9%, preferably 4 to 8%, and more preferably 4.5 to 7.5%.

[0092] In some embodiments of the present invention, by 5+ With Ti 4+ The molar percentage ratio of Nb 5+ / Ti 4+ Controlling the ratio between 0.1 and 0.32 can improve the optical transmittance and glass stability of the glass and optimize the chemical stability of the glass. 5 + / Ti 4+ 0.12 to 0.3, more preferably Nb 5+ / Ti 4+ It is 0.15~0.27.

[0093] Na + It has the function of improving the melting property of glass, has a significant effect on improving the melting effect, and can also reduce the transition temperature of glass. In terms of cation molar percentage, the present invention introduces more than 4.5% Na + To obtain the above effects, Na + The lower limit of the content of Na is 5%, and the more preferred lower limit is 5.5%. + When the content exceeds 10%, the chemical stability and weather resistance of the glass decrease. + The upper limit of the content is 10%, preferably 9%, and more preferably 8.5%.

[0094] K + It has the effect of improving the thermal stability and melting property of glass. In terms of cation molar percentage, the present invention introduces more than 4% K + To obtain the above effects; but if its content exceeds 7%, the devitrification resistance of the glass decreases and the glass density increases. Therefore, in the present invention, K is expressed as a percentage of cations. + The content is 4-7%, preferably K + The content is 4.5 to 6.5%, more preferably 5 to 6%.

[0095] Zr 4+ It is a high-refractive and low-dispersion component that can increase the refractive index of glass and adjust the dispersion, thereby improving the anti-crystallization performance of the glass.4+ When the content of Zr is above 3%, the above effect can be obtained. When it is below 3%, the effect is not obvious. 4+ When the content of Zr is higher than 4.2%, the glass melting becomes more difficult and the melting temperature rises. Furthermore, it will also cause inclusions inside the glass and reduce the light transmittance. 4+ The content is 3-4.2%, preferably Zr 4+ The content is 3-4%.

[0096] Ba 2+ In the present invention, it is an essential component for adjusting the glass refractive index, improving the glass transmittance and strength. 2+ When the content is less than 5%, the effect is not obvious. 2+ The lower limit of the content of Ba is 5.3%, and Ba is more preferably 2+ The lower limit of Ba content is 5.5%; but when its content exceeds 8.7%, the anti-crystallization performance and chemical stability of the glass will deteriorate. 2+ The upper limit of the content is 8.7%, preferably 8.2%, and more preferably 8%.

[0097] Sr 2+ It can increase the stability of glass, improve the anti-crystallization performance of glass, and increase the Abbe number of glass. When its content is less than 2.3%, the effect is not obvious. If its content is higher than 4%, the Abbe number of glass is higher than the design requirement. 2+ The content of Sr is limited to 2.3-4%, preferably Sr 2+ The content is 2.5 to 4%, more preferably 2.5 to 3.5%.

[0098] Al 3+ It can improve the chemical stability of glass to a certain extent, but if its content is too high, the resistance to devitrification and melting of glass will be reduced. 3+ The content of is 3% or less, preferably 1% or less, and more preferably 0.5% or less.

[0099] Y 3+ It is a component that improves the refractive index and chemical stability of the glass and is an optional component in the optical glass of the present invention. 3+ The content of Y is controlled to be less than 3% to improve the anti-devitrification performance of the glass and obtain the desired refractive index and Abbe number. 3+ The upper limit of the content range is 3%, preferably 1%, and more preferably 0.5%.

[0100] The optical glass of the present invention contains Sb3+ As an essential ingredient. Sb 3+ It is a component that keeps the number of bubbles in the glass stable and at a very low level.

[0101] In the optical glass of the present invention, Sb 3+ The content of is 0.03% or less, preferably 0.01 to 0.02%. Within such an extremely limited specific range, the number of bubbles in the glass can be stabilized and reduced to an extremely small amount without deteriorating the coloring property.

[0102] In the optical glass of the present invention, the anion may be O 2- .

[0103] In the optical glass of the present invention, transition metals such as V, Cr, Mn, Fe, Co, Ni, Cu, Ag and Mo, even if contained in a small amount alone or in combination, will cause the glass to be colored and produce absorption at specific wavelengths in the visible light region, thereby reducing the visible light transmittance of the present invention. Therefore, it is preferably not substantially contained, especially in optical glass that requires transmittance at wavelengths in the visible light region.

[0104] Th, Cd, Tl, Os, Be and Se elements have a tendency to be controlled in recent years as harmful chemical substances, and environmental protection measures are necessary not only in the manufacturing process of glass, but also in the processing process and the disposal after productization. Therefore, in the case of paying attention to the impact on the environment, it is preferred that they are not actually contained except that they are inevitably mixed in. Thus, the optical glass does not actually contain substances that pollute the environment. Therefore, even if special environmental countermeasures are not taken, the optical glass of the present invention can also be manufactured, processed and discarded.

[0105] In order to achieve environmental friendliness, the optical glass of the present invention does not contain As and Pb. Although As has the effect of eliminating bubbles and preventing glass from being colored, the addition of As will increase the platinum erosion of the glass on the furnace, especially the platinum furnace, causing more platinum ions to enter the glass, which has an adverse effect on the service life of the platinum furnace. Pb can significantly improve the high refractive index and high dispersion performance of the glass, but both Pb and As are substances that cause environmental pollution.

[0106] In some specific embodiments, the optical glass preferably does not contain F - , P 5+ 、 5+ , Gd 3+ ,Ge 4+ 、Te 4+ One or a combination of two or more of the following. -The volatilization of F components during the melting process will cause environmental pollution, unstable optical constant consistency, and easily cause defects such as stripes on the glass; on the other hand, during the precision molding process, it will also cause the optical glass surface to fog easily. Therefore, the present invention preferably does not introduce F - .P 5+ It is easy to corrode precious metal containers such as platinum, especially phosphate glass containing alkali metals, which is more corrosive; and P 5+ It is easy to volatilize at high temperature, which affects the optical stability of the glass. Therefore, the present invention preferably does not introduce P 5+ . 5+ The price of Ta is very expensive, and from the perspective of practicality and cost, its usage should be minimized. Therefore, the present invention preferably does not introduce Ta 5+ To reduce the material cost of glass, so as to make the preparation cost of optical glass lower. 3+ ,Ge 4+ And Te 4+ The price is also very high, and it is preferably not introduced in the present invention.

[0107] Due to Li + It is not good for the acid resistance and thermal expansion coefficient of the glass, and it is corrosive to the melting container (such as platinum crucible). Therefore, the present invention preferably does not introduce Li + . 3+ The relative molecular mass is very large, and the content of La is high 3+ This will result in an excessively large specific gravity of the glass. Therefore, the present invention preferably does not introduce La 3+ .

[0108] The "not introduced", "not containing" and "0%" recorded in this article mean that the compound, molecule or element is not intentionally added as a raw material to the optical glass of the present invention; however, as raw materials and / or equipment for producing optical glass, there will be certain impurities or components that are not intentionally added, which will be contained in small amounts or trace amounts in the final optical glass, and this situation is also within the scope of protection of the patent of this invention.

[0109] In the present invention, the density ρ of the optical glass is 3.40 g / cm 3 Below; Coloring degree λ 80 / λ5,λ 80 The hardness is 420nm or less, λ5 is 365nm or less, and the hardness HK is 500×10 7 Pa or above. The optical glass water resistance stability D W is level 1; the average linear expansion coefficient of the optical glass is α 20~300℃ 79×10 -7 / K~91×10 -7 / K; the transition temperature Tg of the optical glass is below 545°C, and the sag temperature Ts is below 585°C; the bubble degree of the optical glass is level 0 to 1; and the anti-crystallization performance of the optical glass is level A to B.

[0110] Furthermore, the present invention also provides a method for preparing optical glass, which comprises weighing each component according to a proportion, mixing them evenly, melting them, and then pouring or leaking them into a molding mold, or directly pressing them into shape.

[0111] Specifically, the raw materials of each component of the optical glass (such as oxides, hydroxides, carbonates, nitrates, etc.) are mixed and placed in a melting furnace (such as a platinum crucible, an alumina crucible, etc.) at 1200-1400°C. After melting, fusion, clarification, stirring and homogenization, a homogeneous molten glass without bubbles and undissolved substances is obtained. The molten glass is cast in a mold and annealed, or directly pressed into shape.

[0112] The present invention also provides an optical preform and an optical element, which are formed from the above optical glass according to a method well known to those skilled in the art. Since the optical glass has a medium refractive index, the optical element also has a medium refractive index and can be applied to digital cameras, digital video cameras, camera phones and other devices.

[0113] Example

[0114] The embodiments of the present invention will be described in detail below in conjunction with the examples, but those skilled in the art will appreciate that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0115] In order to further understand the technical solution of the present invention, embodiments of the optical glass of the present invention will now be described. It should be noted that these embodiments do not limit the protection scope of the present invention.

[0116] The optical glasses (Examples 1 to 49) shown in Tables 1 to 5 are prepared by weighing and mixing common raw materials for optical glass (such as yttrium oxide, silicon oxide, calcium carbonate, calcium nitrate, aluminum hydroxide, zirconium oxide, sodium carbonate, potassium carbonate, lithium sulfate, magnesium carbonate, barium carbonate, strontium carbonate, antimony oxide, etc.) according to the ratios of the various embodiments shown in Tables 1 to 3, placing the mixed raw materials in a platinum crucible of a melting device, melting and homogenizing at a temperature of 1250°C, clarifying at a temperature of 1360°C to allow bubbles to fully float, then reducing the temperature of the glass liquid to about 1130°C, pouring or leaking it into a molding mold through a cylindrical pipe, annealing and cooling, and then processing to obtain the optical glass of the present invention.

[0117] Performance Testing

[0118] 1. Refractive index n d , Abbe number υ d

[0119] The refractive index n of the obtained optical glass was measured according to the test method of GB / T7962.1-2010. d , Abbe number υ d Determination of the n listed in the table d ,υ d The data are after annealing at -4°C.

[0120] 2. Knoop hardness HK

[0121] Knoop hardness is measured according to the test method specified in ISO9385.

[0122] 3. Average linear expansion coefficient of glass α 200~300℃

[0123] Measure according to the method specified in GB / T7962.16.

[0124] 4. Transition temperature Tg and relaxation temperature Ts

[0125] Measure according to the method specified in GB / T7962.16.

[0126] 5. Density ρ

[0127] The density of the obtained optical glass was measured according to the test method of GB / T7962.20-2010.

[0128] 6. Coloring degree λ 80 / λ5

[0129] Coloration λ for short-wave transmission spectrum characteristics of optical glass 80 / λ5 represents. 80 It refers to the wavelength when the glass transmittance reaches 80%, and λ5 refers to the wavelength when the glass transmittance reaches 5%.

[0130] 7. Water resistance stability D W

[0131] According to the test method of GB / T 17129, the water resistance stability of the obtained optical glass is tested. W Run the test.

[0132] 8. Acid resistance stability D A

[0133] According to the test method of GB / T 17129, the acid resistance stability of the obtained optical glass chemical stability DA Run the test.

[0134] 9. Bubble degree

[0135] The bubble degree of the obtained optical glass was tested according to GB / T7962.8-2010 Test method for colorless optical glass Part 8: Bubble degree.

[0136] 10. Anti-crystallization performance

[0137] The experimental samples were processed into specifications of 20×20×10mm and polished on both sides. The samples were placed in a crystallization furnace at a temperature of Tg+200℃ and kept warm for 30 minutes. After being taken out and cooled, the two large surfaces were polished again. The crystallization performance of the glass was judged according to Table 1 below, with Grade A being the best and Grade E being the worst.

[0138] Table A Classification and judgment criteria of crystallization

[0139]

[0140] In some embodiments, the anti-crystallization performance of the optical glass of the present invention is above Class B, preferably Class A, and has excellent anti-crystallization performance.

[0141] The refractive index n of the optical glass prepared in Example 1-49 is d , Abbe number υ d , hardness HK, average linear expansion coefficient, transition temperature Tg, sag temperature Ts, density ρ, λ in coloring 80 and λ5, water resistance stability D W , Acid resistance stability D A , anti-crystallization performance and bubble degree are listed in Tables 1-7; the measured data of Comparative Examples AB are listed in Table 8.

[0142] Table 1: Glass components and performance parameters of Examples 1-7

[0143]

[0144] Table 2: Glass components and performance parameters of Examples 8-14

[0145]

[0146] Table 3: Glass composition and performance parameters of Examples 15-21

[0147]

[0148] Table 4: Glass composition and performance parameters of Examples 22-28

[0149]

[0150] Table 5: Glass composition and performance parameters of Examples 29-35

[0151]

[0152] Table 6: Glass composition and performance parameters of Examples 36-42

[0153]

[0154] Table 7: Glass composition and performance parameters of Examples 43-49

[0155]

[0156] Table 8: Glass composition and performance parameters of Comparative Examples A and B

[0157]

[0158] It can be seen from the above examples that the refractive index (n d ) is 1.73~1.83, and the Abbe number (υ d ) is 20-30, and the density ρ is 3.40 g / cm 3 Below; the hardness of optical glass is HK 500×10 7 Pa or above, water resistance stability D W Grade 1, acid resistance stability D A is level 1; the coloring degree of optical glass is λ 80 / λ5,λ 80 is less than 420nm, and λ5 is less than 365nm. In addition, the linear expansion coefficient α of optical glass is 20~300℃ 79×10 -7 / K~91×10 -7 / K.

[0159] The transition temperature Tg of the optical glass is below 630°C, the sag temperature Ts is below 670°C, and the anti-crystallization performance is grade A to B; the bubble degree of the optical glass is grade 0 to 1, and it is suitable for wide application in digital cameras, digital video cameras, camera phones and other devices.

[0160] As can be seen from Table 8, Comparative Example A contains 3% Li + , chemical stability deteriorates, Tg, Ts decrease, and crystallization performance deteriorates, which is not conducive to production, and does not meet the durability of wind and rain, reagents, etc., which has a great impact on use. Comparative Example B contains 0.5% Sb 3+ , the coloring becomes worse.

[0161] It should be noted that, although the technical solution of the present invention is introduced with specific examples, those skilled in the art will appreciate that the present invention should not be limited thereto.

[0162] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and variations will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or technical improvements in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.

Claims

1. An optical glass, characterized in that: It contains the following components in terms of cationic molar percentage: And 4+ :36~47%; Of 4+ :26~31.5%; Nb 5+ :3~9%; That + :4.5~10%; K + :4~7%; Zr 4+ :3~4.2%; Not 2+ :5~8.7%; Sr 2+ :2.3~4%; Al 3+ :0~3%; Y 3+ :0~3%; Sb 3+ :0~0.03%; The refractive index of the optical glass is 1.73-1.83, and the Abbe number is 20-30.

2. The optical glass according to claim 1, characterized in that: The optical glass comprises the following components in terms of cation molar percentage: And 4+ :38~46.5%; Of 4+ :26~31%; Nb 5+ :4~8%; That + :5~9%; K + :4.5~6.5%; Zr 4+ :3~4%; Not 2+ :5.3~8.2%; Sr 2+ :2.5~4%; Al 3+ :0~1%; Y 3+ :0~1%; Sb 3+ :0.01~0.02%。 3. The optical glass according to claim 2, characterized in that: The optical glass comprises the following components in terms of cation molar percentage: And 4+ :39~46%; Of 4+ :26.5~30.5%; Nb 5+ :4.5~7.5%; That + :5.5~8.5%; K + :5~6%; Zr 4+ :3~4%; Not 2+ :5.5~8%; Sr 2+ :2.5~3.5%; Al 3+ :0~0.5%; Y 3+ :0~0.5%; Sb 3+ :0.01~0.02%。 4. The optical glass according to any one of claims 1 to 3, characterized in that: The optical glass does not contain F - , P 5+ 、 5+ , Gd 3+ , Li + ,La 3+ ,Ge 4+ 、Te 4+ One or a combination of two or more.

5. The optical glass according to any one of claims 1 to 4, characterized in that: Ti 4+ With Si 4 The molar percentage ratio of Ti 4+ / Si 4 0.55~0.85; Nb 5+ With Ti 4+ The molar percentage ratio of Nb 5+ / Ti 4+ It is 0.1~0.

32.

6. The optical glass according to any one of claims 1 to 5, characterized in that: The density of the optical glass is 3.40 g / cm 3 the following; The coloration degree λ of the optical glass 80 / λ5,λ 80 is below 420nm, and λ5 is below 365nm; The hardness HK of the optical glass is 500×10 7 Pa or above.

7. The optical glass according to any one of claims 1 to 6, characterized in that: The water resistance stability of the optical glass is level 1; The acid resistance stability of the optical glass is level 1; The anti-crystallization performance of the optical glass is A-B grade; The bubble degree of the optical glass is 0-1 level.

8. A method for preparing the optical glass according to any one of claims 1 to 7, characterized in that: The method comprises weighing each component of the optical glass according to a proportion, mixing the components evenly, melting the components, and then pouring or leaking the components into a forming mold, or directly pressing the components into a forming mold.

9. An optical preform, characterized in that: The optical glass comprises the optical glass according to any one of claims 1 to 8.

10. An optical element, characterized in that: The optical glass comprises the optical glass according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Optical glass

    CN101636359A

  • Optical glass

    CN102471130A

  • Optical glass, optical glass blank, glass material for press molding use, optical element, and methods respectively for producing said products

    CN104981439A

  • Glass composition and chemical toughened glass

    CN107963808A

  • Optical glass, optical glass blank, glass material for press molding, optical element, and methods for producing same

    CN108178509A